Metafisika Mediasi Teknologis: Kritik Atas Filsafat Teknologi Klasik - Imam Wahyudi; Rangga Kala Mahaswa (Jurnal Filsafat "WISDOM", 2020)
This paper aims to propose philosophical criticism toward 'classical' thinking on philosophy of technology. This set of thinking tends to be trapped in the distinction between subject-object and romantic-pessimisms on the existence of technological dominance. The authors objective is to provide comprehensive understanding through contemporary approaches in philosophy concerning technological mediation. The study employs factual historical analysis and philosophical reflection to understand technological mediation patterns. The result maps point of view that develops a metaphysical orientation of technological mediation in terms of several approaches. Postphenomenological approaches technological mediation in a relational and intentional context rather than providing a subject-object distinction. Actor-network theory improves the asymmetrical relation of humans and non-humans. Simondon and Harman provide for ontological analysis of tools and technology in human relationships. Critical theory of technology opens the chance that technological relations are not only neutral-instrumental but have transformative and emancipatory power. Therefore, the technological mediation approach can become a new subject in the metaphysics of technology discourse in overcoming the limitations of the classical philosophy of technology.